Design and preparation of an ultra-high temperature ceramic by in-situ introduction of Zr₂[Al(Si)]₄C₅ into ZrB₂-SiC : investigation on the mechanical properties and oxidation behavior - Yu, Lei (2021)
Novel ZrB2-matrix composites were designed and prepared by in-situ introducing SiC and Zr2[Al(Si)]4C5 simultaneously for the first time. The obtained composites were dense and showed good mechanical properties, especially the strength and toughness, 706 MPa and 7.33 MPa·m1/2, respectively, coupled with high hardness of 21.3 GPa, and stiffness of 452 GPa. SiC and Zr2[Al(Si)]4C5 constituted a reinforcing system with synergistic effects including grain refinement, grain pull-out as well as crack branching, bridging, and deflection. Besides, the oxidation results of the composites showed that the oxidation kinetics followed the parabolic law at 1600 ℃, and the oxidation rate constants increased with the increase of Zr2[Al(Si)]4C5 content. The formation and evolution model of the oxidation structure was also investigated, and the oxide scale of the composite exhibited a three-layer structure.